If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(t) = x + 120(t + -6) Multiply x * t tx = x + 120(t + -6) Reorder the terms: tx = x + 120(-6 + t) tx = x + (-6 * 120 + t * 120) tx = x + (-720 + 120t) Reorder the terms: tx = -720 + 120t + x Solving tx = -720 + 120t + x Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-120t' to each side of the equation. -120t + tx = -720 + 120t + -120t + x Combine like terms: 120t + -120t = 0 -120t + tx = -720 + 0 + x -120t + tx = -720 + x Reorder the terms: 720 + -120t + tx + -1x = -720 + x + 720 + -1x Reorder the terms: 720 + -120t + tx + -1x = -720 + 720 + x + -1x Combine like terms: -720 + 720 = 0 720 + -120t + tx + -1x = 0 + x + -1x 720 + -120t + tx + -1x = x + -1x Combine like terms: x + -1x = 0 720 + -120t + tx + -1x = 0 The solution to this equation could not be determined.
| 2x=90-3x | | 0=1/3x-4 | | (6y-2)+y=180 | | 7x-2=11x+1 | | y-5=150(x+4) | | 3(x+2)=3(2x+4) | | (X-2+4i)(x-2-4i)= | | 12m+3n-5m+10n= | | X*2/3=8/9 | | 9(3b+7)-(7b+2)=-59 | | 10x-5+8x+5=180 | | 9(y+5+3)=108 | | (2x+7i)(2x-7i)= | | f(3)=2f(1) | | A+17=4(A-2)-5+3A | | x^4-7x^3-10x^2+7x+1=0 | | 4x+8=202 | | 8w+5=4(2+1)w | | 0.09xX=77.01 | | C/4=11 | | 13y+7y+(6y+6)=34 | | -6x+-12=42 | | x^2-55x+204=0 | | 0.09xX=62.95 | | 2y+25-19=0 | | 5x+2=x+8T | | 2-3x=-5x+16 | | 6x+13=x+8 | | 5x-4=2(4x+4)-3 | | n/5.5=2 | | 7/8x5/9 | | 2x+5=3(2x-4) |